2019
DOI: 10.1002/pra2.132
|View full text |Cite
|
Sign up to set email alerts
|

“For the benefit of all students”: Student trust in higher education learning analytics practices

Abstract: Learning analytics is a sociotechnical practice that seeks new insights from mining and analyzing student data. As new flows of student data emerge and granular information about student life becomes more accessible, there is a growing call to address student privacy and related issues. This poster reports emerging results from over 100 interviews with undergraduate students regarding their privacy perceptions especially with regard to trust.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In the context of high levels of trust in the institution's reputation and track record, students' desire to have and maintain control of data becomes less important. The latter finding is confirmed in the research by Jones and Afnan (2019) who found that students' trust in the university was based on the belief that "universities are seen as good institutions who employ trustworthy people" (p. 683). Though students trust universities, the research points out that this trust needs to be sustained through ensuring secure data and information systems to prevent breaches, controlling the sharing of the data and limiting the collection of data for learning analytics purposes to what is considered to be "useful [.…”
Section: Trust In Learning Analytics: a Brief Overviewmentioning
confidence: 66%
“…In the context of high levels of trust in the institution's reputation and track record, students' desire to have and maintain control of data becomes less important. The latter finding is confirmed in the research by Jones and Afnan (2019) who found that students' trust in the university was based on the belief that "universities are seen as good institutions who employ trustworthy people" (p. 683). Though students trust universities, the research points out that this trust needs to be sustained through ensuring secure data and information systems to prevent breaches, controlling the sharing of the data and limiting the collection of data for learning analytics purposes to what is considered to be "useful [.…”
Section: Trust In Learning Analytics: a Brief Overviewmentioning
confidence: 66%